BLOOD SERUM MICRO- AND MACROELEMENTS DISORDERS IN PATIENTS WITH CHRONIC HEPATITIS AND HEPATIC CIRRHOSIS - Khvorostinka, V.N.; Lakhno, O.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
It was investigated blood level of bioelements and the links between their concentrations and antioxidative defense system in patients with chronic diffusive liver diseases. It was determined reduced concentration of potassium, natrium, calcium, magnesium, zinc, iron and increasing level of copper. Bioelemental disorders depended on the pathological process activity and stage of disease.